2018
DOI: 10.1186/s12886-018-0935-7
|View full text |Cite
|
Sign up to set email alerts
|

Implantable collamer lens surgery in patients with primary iris and/or ciliary body cysts

Abstract: BackgroundThe prevalence of primary iris and/or ciliary body cysts is common in myopia, though asymptomatic in nearly all cases. It’s a very valuable thing to study the clinical safety and reliability of implantable collamer lens (ICL) surgery in patients with primary iris and/or ciliary body cysts.MethodsA total of 108 patients (201 eyes) were included in this retrospective study. All eyes had been implanted with V4c implantable collamer lens (ICLV4c). According to the eyes with or without primary iris and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
(17 reference statements)
4
14
0
Order By: Relevance
“…Additionally, the sample size of our study was larger (83 eyes vs. 46 eyes) than theirs, and the crystalline LT was easier to measure. To identify the presence of ciliary body cysts, UBM is an important preoperative examination before ICL implantation [ 18 , 44 ]. Therefore, our formula may be applied conveniently, without an additional anterior segment Optical Coherence Tomography (AS-OCT) examination.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the sample size of our study was larger (83 eyes vs. 46 eyes) than theirs, and the crystalline LT was easier to measure. To identify the presence of ciliary body cysts, UBM is an important preoperative examination before ICL implantation [ 18 , 44 ]. Therefore, our formula may be applied conveniently, without an additional anterior segment Optical Coherence Tomography (AS-OCT) examination.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative NPACD, TPACD, NACA, and TACA were lower than pre-operative measurements in eyes with iris and/or ciliary body cysts in the present study. Li and associates ( 30 ) found no significant differences in post-operative AOD 500 and TIA between eyes with and without cysts. In Li's study, cysts were found predominantly in the inferior and temporal quadrants, while cysts were primarily located in the horizontal direction in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies on angle opening measurements in eyes undergoing ICL implantation are summarized in Table 3 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. With regard to UBM measurements, Chung et al demonstrated that AOD500 and TIA were significantly smaller than preoperative values by 41.5% and 31.8%, respectively, 1 month postoperatively and that no significant progressive changes were observed thereafter [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al showed that the mean ratios of reduction of AOD500 and TIA were 27.32% and 28.41%, respectively, after ICL implantation in eyes with low anterior chamber depth (<2.8 mm) [ 11 ]. Li et al mentioned that the postoperative AOD500 and TIA showed a statistical reduction in ICL-V4c-implanted eyes having primary iris and/or ciliary body cysts [ 15 ]. With regard to AS-OCT measurements, Fernández-Vigo et al reported that considerable angle narrowing was detected 1 month postoperatively and that this narrowing remained stable at 3 months after ICL V4c implantation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%